2003
DOI: 10.1177/000313480306900208
|View full text |Cite
|
Sign up to set email alerts
|

The Role of [18F]Fluorodeoxyglucose Positron Emission Tomography Imaging in the Evaluation of Hepatocellular Carcinoma

Abstract: It has been well established that hepatocellular carcinomas (HCCs) accumulate [18F]fluorodeoxy-glucose (FDG) to varying degrees; this is thought to be due to differing amounts of FDG-6-phosphatase activity. The purpose of this study was to evaluate the impact of FDG imaging on the management of patients diagnosed with hepatocellular carcinoma. We conducted a retrospective review of the clinical data of 91 consecutive patients diagnosed with HCC who underwent FDG-positron emission tomography (PET) imaging betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…The relevance of such an investigation may be further fueled by the fact that those tumor entities commonly spread toward the liver, 27 , 40 , 41 where 18 F-FDG can only provide limited information on organ-specific involvement. 8 As such, the present findings may provide a rationale to design future clinical trials focusing on those tumors of the digestive system, which often present with liver-dominant disease.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The relevance of such an investigation may be further fueled by the fact that those tumor entities commonly spread toward the liver, 27 , 40 , 41 where 18 F-FDG can only provide limited information on organ-specific involvement. 8 As such, the present findings may provide a rationale to design future clinical trials focusing on those tumors of the digestive system, which often present with liver-dominant disease.…”
Section: Discussionmentioning
confidence: 78%
“…For tumors of the digestive tract, current guidelines recommend conventional imaging (including CT or MRI) and various PET agents, such as 18 F-FDG or 68 Ga-DOTATOC 5–7 . However, cirrhotic changes may significantly hamper lesion detection by CT/MRI, whereas increased background activity and uptake in normal organs on 18 F-FDG PET may mask other sites of disease within the liver, spleen, or gut 8 . Of note, cancer-associated fibroblasts (CAFs) have been identified to orchestrate development, angiogenesis, and tumor invasion in the majority of digestive tumors, thereby rendering CAFs as a suitable target for reliable assessment of the current status quo 9 .…”
mentioning
confidence: 99%
“…8 Previous reports have shown that the sensitivity of this method for the detection of HCC is relatively limited (50%–65%), because of the low sensitivity for well‐ and moderately differentiated HCC. 9 , 10 Furthermore, FDG uptake and tumor size are strongly correlated. FDG‐PET/CT exhibits low sensitivity for the detection of HCC with a diameter ≤5 cm; hence, it may not be effective for the diagnosis of such tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding FDG‐PET/CT findings for PHNEC, Mitamura et al showed that FDG‐PET/CT sensitivity was dependent on the neuroendocrine tumor (NET) grade, namely 57% and 66% for NET grade 1 and grade 2, respectively 8 . Previous reports have shown that the sensitivity of this method for the detection of HCC is relatively limited (50%–65%), because of the low sensitivity for well‐ and moderately differentiated HCC 9,10 . Furthermore, FDG uptake and tumor size are strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Este perfil enzimático está invertido en los hepatocarcinomas indiferenciados. La actividad de la enzima Glucosa 6-fosfatasa se encuentra muy reducida en este tipo de neoplasias, adicionalmente existe una alta concentración de transportadores de glucosa en la membrana (GLUT), contribuyendo estos dos fenómenos, a un incremento en la internalización de glucosa marcada con 18F y su posterior fosforilación en la vía metabólica de la glucosa, quedando atrapada con 18F-FDG-6-fosfato (7).…”
Section: Figura 1 Cortes Axiales De Tc Sin Contraste (A) Y Con Contra...unclassified